2022
DOI: 10.1038/s41467-022-28882-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of a SARS-CoV-2 omicron spike protein ectodomain

Abstract: The omicron variant of SARS-CoV-2 has been spreading rapidly across the globe. The virus-surface spike protein plays a critical role in the cell entry and immune evasion of SARS-CoV-2. Here we determined the 3.0 Å cryo-EM structure of the omicron spike protein ectodomain. In contrast to the original strain of SARS-CoV-2 where the receptor-binding domain (RBD) of the spike protein takes a mixture of open (“standing up”) and closed (“lying down”) conformations, the omicron spike molecules are predominantly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 46 publications
11
116
0
Order By: Relevance
“…Enhanced ACE2 binding by the RBD may facilitate the omicron variant’s infection of the respiratory tracts. Moreover, we recently showed that whereas the RBD in the prototypic spike protein takes a mixture of standing-up position for receptor binding and lying-down position for immune evasion, the RBD in the omicron spike protein predominantly takes a standing-up conformation ( 26 ), which should further enhance ACE2 binding. Thus, the omicron variant appears to have evolved the following two strategies for enhanced ACE2 binding: evolution of the RBD and opening up of the spike.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced ACE2 binding by the RBD may facilitate the omicron variant’s infection of the respiratory tracts. Moreover, we recently showed that whereas the RBD in the prototypic spike protein takes a mixture of standing-up position for receptor binding and lying-down position for immune evasion, the RBD in the omicron spike protein predominantly takes a standing-up conformation ( 26 ), which should further enhance ACE2 binding. Thus, the omicron variant appears to have evolved the following two strategies for enhanced ACE2 binding: evolution of the RBD and opening up of the spike.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, B.1.529 has generally been shown to be less fusogenic and with lowered S1/S2 cleavage than the other variants (7)(8)(9)(10)(11)(12)(13)(14), especially in comparison to B.1.617.2 (Delta) the predominant variant at the time of B.1.529 emergence. Conversely, it has also been reported that the furin motif in the recombinant Omicron spike ectodomain is more efficient than that in the prototypic spike ectodomain (15), and many details of the cleavage-activation process of SARS-CoV-2 B. 1.529 (Omicron) remain to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…While, to date, no conclusive explanation has been provided concerning the benefits associated with the presence of ins214EPE in BA.1, it is very likely that this small insertion, in combination with other NTD non-synonymous mutations, had a significant impact on the structure of the spike protein in BA.1. These alterations to the original primary sequence of the SARS-CoV-2 spike protein might have possibly contributed to the enhanced inter-domain and inter-subunit packing, as well as to the higher accessibility for ACE2 binding, driven by its higher predisposition towards an open configuration (Ye et al, 2022). From this perspective, the acquisition of RIR1 insertions such as L, LIII and others, might be also interpreted as a trait conferring increased stability to the BA.2 spike trimer.…”
Section: Resultsmentioning
confidence: 99%